(untitled) (Faridpur Medical College Journal, 2020)
Breast cancer stands first in the incidence of malignancy in women. Enormous studies have been conducted worldwide regarding hormone receptor status in breast cancer. The study was done in the department of pathology in Khulna Medical College, Khulna to compare the clinicopathologic features with four breast cancer subtypes defined by immunohistochemistry (IHC) expression of estrogen receptor (ER) or progesterone receptor (PR) and human epidermal growth factor receptor 2 (Her2): ER/PR+, Her2+; ER/PR+, Her2_; ER/PR_, Her2+; and ER/PR_, Her2_ and to evaluate hormone receptor status in breast cancer to estimate a patient’s response to endocrine therapy and their prognosis for better clinical outcomes. It is a retrospective observational study from 1st January, 2015 to 31st December, 2017. A total 378 invasive breast cancer subjects who underwent diagnostic tests for hormone receptors status were included in this study. Clinical and pathologic features and survival of the four subtypes were compared. Data of oestrogen, progesterone and human epidermal growth factor receptor 2 expression statuses was analyzed. Overall record of 378 patients was studied of whom 43% were identified to have positive hormone receptor status. The age of the patients ranged from 24 to 86 years with 65% in 25-50 years, 30.8% in 51-75 years and 4.08% in 76- 100 years. Fiftyeight percent were diagnosed as Stage III, 37% Stage II and 5.3% Stage IV. Those diagnosed with oestrogen receptor (positive status) were 10.7%, human epidermal growth factor receptor 2 over-expression 8.7%, oestrogen/progesterone hormone receptor positivity 51% and 23.4% patients were positive for all the three receptors. The triple negative subtype has the worst overall and disease free survival. Faridpur Med. Coll. J. Jan 2019;14(1): 8-12